Modelling the threshold voltage of p‐channel enhancement‐mode GaN heterostructure field‐effect transistors. Issue 4 (1st April 2018) - Kumar, Ashwani; De Souza, Maria Merlyne
Abstract : p‐Channel gallium nitride (GaN) metal–oxide–semiconductor heterostructure field‐effect transistors utilising a polarisation induced two‐dimensional hole gas operate inherently in depletion mode. The condition for their conversion to enhancement‐mode operation is examined via analytical expressions for the threshold voltage and verified via technology computer‐aided design (TCAD) simulations. Between the two heterostructures: (i) conventional GaN/aluminium GaN (AlGaN)/GaN and (ii) alternate AlGaN/GaN/AlGaN/GaN examined in this work, the authors demonstrate at higher threshold voltage ( > − 2 V ), the alternate heterostructure can potentially achieve a higher on‐current by a factor of 2 of ( ∼ 30 mA / mm ), without degradation in the on–off‐current ratio, expected ideally to be of the order of ∼ 12 .